Enhanced Electrochemical Properties of Non-stoichiometric Layered Perovskites, Sm1−xBaCo2O5+d, for IT-SOFC Cathodes - Kim, Chan Gyu; Woo, Sung Hun; Song, Kyeong Eun; Baek, Seung-Wook; Kang, Hyunil; Choi, Won Seok; Kim, Jung Hyun (Frontiers in Chemistry, 2021)
In this study, electrochemical properties of layered perovskites having non-stoichiometric compositions (Sm1-xBaCo2O5+d, x=0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.10, and 0.15) were analyzed for the direct application of cathode materials for Intermediate Temperature-operating Solid Oxide Fuel Cells (IT-SOFC). From the Sm1-xBaCo2O5+d oxide systems calcined at 1100oC for 8 hours, single phase (SmBaCo2O5+d, SBCO_1) was maintained only in the case of the x=0 composition. In the compositions of x=0.05-0.10, BaCoO2.6 was mixed with the pattern of SBCO. In addition, in the composition of x=0.15, it was confirmed that BaCoO2.6 and CoO phases coexisted with SBCO. In the compositions of Sm1-xBaCo2O5+d, the overall Area Specific Resistance (ASR) values decreased as the removal amount of Sm increased from x=0 to 0.10; then, the values increased for compositions from x=0.15. For example, the ASRs of SBCO_1, Sm0.95BaCo2O5+d (SBCO_0.95), Sm0.90BaCo2O5+d (SBCO_0.90), and Sm0.85BaCo2O5+d (SBCO_0.85) measured at 600oC were 0.301, 0.147, 0.119, and 0.179 Ωcm2, respectively. In particular, SBCO_0.90 was found to have an excellent ASR property of about 0.035 Ωcm2 at 700oC. Typical properties of the metal–insulator transition (MIT) electrical conductivity were shown in all measured compositions. The temperature at which MIT occurred increased as the non-stoichiometric composition increased.